Analysis of dynamic measurements in piles - Fernando, I. C. R.; Balasubramaniam, A.S.; Noppadol Phien-Wej; Bergado, Dennes T.; Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1993)
With the development of modern electronic testing and recording equipment, stress wave measurements on piles became possible. Today, stress wave measurement or the dynamic measurement techniques are used extensively to predict, the pile drivability criteria, the static load capacity, and the stresses generated and any possible damages in piles. This study is the first attempt at AIT to critically evaluate the theory and the practice of two of the most popular dynamic measurement techniques presently being used in Bangkok (CASE and CAPWAPC methods). The static load test data on eighteen piles are concurrently compared with the results from the use of the CAPWAPC program. Also, CASE and CAPW APC analysis on additional seventy-four piles are used to obtain direct correlations between the two methods for a variety of pile types, lengths and tip conditions. Useful correlations are made (to the benefit of practising geotechnical engineers) in predicting the static load capacity from the dynamic test measurements. Also, a method of obtaining the static load settlement curves from CAPWAPC analysis is presented. Finally, additional information regarding damping factors and typical resistance distributions in individual soil layers, and a modified guideline for the CAPW APC user are presented which will reduce the effort and time needed, and to improve the quality of the use of CAPW APC program in dynamic pile testing.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Piling (Civil engineering) -- Testing